2016
DOI: 10.1080/21645515.2016.1168953
|View full text |Cite
|
Sign up to set email alerts
|

School-located vaccination for adolescents: Past, present, and future and implications for HPV vaccine delivery

Abstract: Adolescents were first specifically targeted for school-located vaccination (SLV) in the 1990s when hepatitis B catch-up vaccination was recommended for all adolescents. SLV affords the opportunity to access adolescents at a time when their activities have developmental import and the patients have the capacity to decline repeatedly missing school and extracurricular events to get vaccinated. As noted above, SLV has been primarily reserved for brief catch-up interventions among youth, with routine vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…Published studies have also reported some school districts requiring separate consent forms for each adolescent vaccine, requiring parents to be in attendance for all immunizations, and only allowing certain schools to participate, with students and parents needing to travel to other schools to participate. [23][24][25][26] Each of these factors might pose significant barriers to the success of SLV programs.…”
Section: Challenges To Working With School Districtsmentioning
confidence: 99%
“…Published studies have also reported some school districts requiring separate consent forms for each adolescent vaccine, requiring parents to be in attendance for all immunizations, and only allowing certain schools to participate, with students and parents needing to travel to other schools to participate. [23][24][25][26] Each of these factors might pose significant barriers to the success of SLV programs.…”
Section: Challenges To Working With School Districtsmentioning
confidence: 99%
“…19 In other countries, SLV is widely used to administer a broad range of vaccinations, including HPV vaccine. 20,21 SLV efforts face certain challenges including potential disruption to the school day as well as the need to receive buy-in from educational authorities, obtain parental consent, verify insurance status, purchase vaccine for non-VFC eligible students, use outside individuals to administer vaccinations, and notify PCPs that their patients were vaccinated in school. 19,22,23 School-based health centers (SBHCs) often provide health care services to youth who have financial, cultural, or geographic barriers to receiving care elsewhere.…”
Section: T a G G E D P What This Narrative Review Addsmentioning
confidence: 99%
“…In US school-located vaccination models, parents provide consent for their children to be vaccinated by trained community vaccinators at school. 38,39 Because school-located health clinics are uncommon in the United States, we consider the model of holding mass vaccination days, which would potentially reach those ages 11 to 13 who attend a public school (87%). 40 The costs for schoollocated vaccination include time and resources to create information materials, obtain permission from parents, schedule the event, administer the vaccination, and process insurance claims for privately insured adolescents.…”
Section: School-located Vaccinationmentioning
confidence: 99%